The Challenge in Diagnosis and Management of Secondary Conjunctival Cysts - Nurlistyani, Dinda Puspita; Lutfi, Delfitri (Universitas Airlangga, 2024)
Introduction: Conjunctival cysts can be categorized as primary or secondary. This report emphasizes difficulties in diagnosing secondary conjunctival cysts and distinguishing them from other conjunctival lesions like conjunctival benign reactive lymphoid hyperplasia (BRLH). Case Presentation: A 43-year-old male had a painless progressive conjunctival mass for four months. He took anti-aging and muscle-enhancing injections for a year and changed the product brand four months ago. Our examination revealed a conjunctival translucent mass with distinct margins and surface-feeding vessels without visual disturbance. We provisionally diagnosed it as a conjunctival cyst with a differential diagnosis of BRLH. We treated the patient with oral methylprednisolone and dexamethasone eye drops and discontinuation of anti-aging injections. The mass completely disappeared after one month of treatment. Conclusions: This case presented a diagnostic challenge due to the presence of a feeding vessel, which indicated inflammation. This made differentiating from inflamed conjunctival masses, such as BRLH, difficult. The patient had a history of suspected inflammation from changing the brand of injectable drug. Initially, we used steroids to reduce inflammation and prevent mass growth, but surprisingly, the lesion completely disappeared. If it recurs, a biopsy may be needed to identify the exact cause, as we have not ruled out BRLH. Secondary conjunctival cysts can result from toxins, trauma, or allergies. A thorough history taking, eye examination, and biopsy may be necessary to rule out other causes of inflamed conjunctival masses.